Ethanol Production from Extruded Thermoplastic Maize Meal by High Gravity Fermentation with Zymomonas mobilis. (3rd November 2014) - Peralta-Contreras, Mayeli; Aguilar-Zamarripa, Edna; Pérez-Carrillo, Esther; Escamilla-García, Erandi; Serna-Saldívar, Sergio Othon
Abstract : A comparative study of extruded and ground maize meals as raw materials for the production of regular (12°P) and high gravity (20°P) worts was devised. Extruded water solubility index (WSI) was higher (9.8 percentage units) and crude fat was lower (2.64 percentage units) compared to ground maize. Free-amino nitrogen compounds (FAN), pH, and glucose were evaluated in regular and high gravity worts produced from ground or extruded maize. Extrusion improved glucose content and ethanol yield. In 20°P mashes, extrusion is enhanced by 2.14% initial glucose compared with regular ground mashes. The 12°P and 20°P extruded treatments averaged 12.2% and 8.4% higher ethanol, respectively, compared to the uncooked counterpart. The 20°P worts fermented with Zymomonas mobilis produced 9.56% more ethanol than the 12°P counterpart. The results show that the combination of extrusion and fermentation of 20°P worts improved ethanol yield per kg flour until 20.93%. This pretreatment stimulates Z. mobilis fermentation efficiency.